Prognostic Relevance and Function of MSX2 in Colorectal Cancer - Jiancheng Liu; Huaying An; Wei Yuan; Qiang Feng; Lianzhen Chen; Jie Ma (Journal of Diabetes Research)
Colorectal cancer patients with diabetes had the high risks of total mortality. High expression of MSX2 is related to development of diabetes. There are few reports about the clinical implications and function of MSX2 in colorectal cancer (CRC). The purpose of this study is to investigate the relationship between the expression of MSX2 and clinical relevance and discover the possible mechanism of MSX2 in the development of CRC. Compared with adjacent tissues, the expression of MSX2 was higher in tumor tissues in both mRNA and protein levels (P<0.01). Kaplan-Meier survival analysis showed that high mRNA expression of MSX2 was associated with short survival time (P=0.013). Chi-squared test analysis indicated that MSX2 expression was related to tumor size (P=0.04), tumor locus (P=0.025), clinical stage (P<0.001), tumor invasion (P=0.003), lymphatic metastasis (P=0.01), and distant metastasis (P=0.033). In vitro experiments demonstrated that knockdown of MSX2 expression attenuated cell proliferation and invasion, promoted cell cycle arrest and apoptosis, and inactivated Akt phosphorylation. In conclusion, MSX2 played a crucial role in the progression of CRC and may be a potential novel prognostic factor and therapeutic target for CRC therapy. Our work may provide certain enlightenment for investigating the mechanism of MSX2 in the process of diabetes.